2011
DOI: 10.1080/00981389.2010.506411
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Social Worker in the Adult Critical Care Unit: A Systematic Review of the Literature

Abstract: Social workers provide care to patients and families in the adult critical care unit. We conducted a systematic review of the literature to more clearly identify the role of the social worker practicing in the intensive care unit. We conducted a comprehensive search of the literature using the Pubmed, Embase, ISI, Scopus, and Social Work Abstracts databases using the terms "intensive care," "critical care," and "social work." Articles were selected for review if they met the following criteria: formal studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…Social workers are aptly trained to recognize the issues impacting vulnerable populations and to work with other health providers who are responsible for the quality of the medical care that impacts the dying experience. Although the social worker's role in health care settings traditionally entail facilitating communication between patients and medical team members (Hartman-Shea, Hahn, Fritz Kraus, Cordts, & Sevransky, 2011), all providers need to actively engage in advocacy in order to improve overall health outcomes and the quality of the dying experience. This entails assessing patients' needs to determine whether or not they have an adequate support system especially regarding EOL care plans which are often dependent upon the availability of family members for support.…”
Section: Discussionmentioning
confidence: 99%
“…Social workers are aptly trained to recognize the issues impacting vulnerable populations and to work with other health providers who are responsible for the quality of the medical care that impacts the dying experience. Although the social worker's role in health care settings traditionally entail facilitating communication between patients and medical team members (Hartman-Shea, Hahn, Fritz Kraus, Cordts, & Sevransky, 2011), all providers need to actively engage in advocacy in order to improve overall health outcomes and the quality of the dying experience. This entails assessing patients' needs to determine whether or not they have an adequate support system especially regarding EOL care plans which are often dependent upon the availability of family members for support.…”
Section: Discussionmentioning
confidence: 99%
“…Social workers are commonly a part of the multidisciplinary team in ICUs throughout Australia. The primary role of the social worker in ICU is focused on crisis intervention, psychosocial assessment, support and counselling as well as providing practical assistance (Hartman-Shea et al, 2011). This is similar in the Australian ICU context.…”
Section: Setting and Samplementioning
confidence: 97%
“…Families that receive coordinated care may be able to better care for the patient and deal with the emotional stress caused by the experience (Åstedt-Kurki, Lehti, Tarkka, & Paavilainen, 2004;Nelms & Eggenberger, 2010). In their systematic review, Hartman-Shea, Hahn, Fritz Kraus, Cordts, and Sevransky (2011) found that the social worker is a key facilitator of communication in health care. The extensive engagement with families during the time a family member is receiving medical care requires an initial assessment and subsequent understanding of families' communication patterns in order to effectively share information (Rose & Shelton, 2006).…”
Section: Principle 3: Individuals and Families Build On Their Strengtmentioning
confidence: 97%